2008
DOI: 10.1177/1533317508321909
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Differences in the Occurrence of Alzheimer's Disease Mortality: United States Versus Puerto Rico

Abstract: Background Alzheimer’s disease (AD) is the most prevalent type of dementia. Although the pathobiology of AD is still not understood, certain risk factors have been identified. The most asserted risk factors are age and genetics. Here, the age-adjusted AD mortality in Puerto Rico (PR) and United States (US) from 1999 to 2004 was analyzed, using the Tenth International Classification of Disease coding system. Method The numbers of deaths was obtained from the National Center for Health Statistics (NCHS) multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Previously, we found that the mortality rate associated with AD of Puerto Ricans living in Puerto Rico is higher than that for Puerto Ricans living in the US [15]. Geographical differences in mortality rate in Puerto Rico were identified, where some regions had lower or comparable rates to that reported in the US, while other regions showed significantly higher mortality rates associated with AD [15]. The underlying causes of the differential mortality rates and clinical profiles of AD patients in Puerto Rico are still unknown.…”
Section: Epidemiology Of Ad In the Latino Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we found that the mortality rate associated with AD of Puerto Ricans living in Puerto Rico is higher than that for Puerto Ricans living in the US [15]. Geographical differences in mortality rate in Puerto Rico were identified, where some regions had lower or comparable rates to that reported in the US, while other regions showed significantly higher mortality rates associated with AD [15]. The underlying causes of the differential mortality rates and clinical profiles of AD patients in Puerto Rico are still unknown.…”
Section: Epidemiology Of Ad In the Latino Populationmentioning
confidence: 99%
“…The annual average incidence of dementia among the Mexican population in Sacramento, CA was estimated at 0.8%, while Caribbean Hispanics in North Manhattan ranged from 2.3 to 5.3% based on different studies [1215]. Notably, a study conducted in Philadelphia showed that Latinos have more severe symptomatology associated with AD than any other ethnic group studied [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies of Puerto Ricans, living in the island of Puerto Rico, indicated that the mortality rate associated with AD is significantly higher than the one registered in the United States. 15 Moreover, the mortality associated with AD of Puerto Ricans in Puerto Rico is higher than that for Puerto Ricans living in the United States. 15 However, geographical analysis of mortality rate in Puerto Rico identified some regions with lower or comparable rate to the one reported in the United States, while other regions showed significantly higher mortality rate associated with AD.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Moreover, the mortality associated with AD of Puerto Ricans in Puerto Rico is higher than that for Puerto Ricans living in the United States. 15 However, geographical analysis of mortality rate in Puerto Rico identified some regions with lower or comparable rate to the one reported in the United States, while other regions showed significantly higher mortality rate associated with AD. 15 The underlying cause(s) of the differential mortality rate and the clinical profile of AD patients in Puerto Rico are still unknown.…”
Section: Introductionmentioning
confidence: 99%